Karakter Kualitatif dan Kuantitatif Beberapa Varietas Paria (Momordica charantia L.) di Dataran Rendah - Huda, Nabila Farah; Megawati, Sari; Rajiman, Rajiman (Jurnal Agroteknologi (Agronu), 2025)
Bitter melon (Momordica charantia L.) is a commodity with quite high market demand and requires the fulfillment of seed needs that are in accordance with farmer preferences. This study aims to determine the superiority of qualitative and quantitative characters of several varieties of bitter melon in the lowlands. This study was conducted from October 2024 to January 2025 at the Trial Land of CV Trias Putra Agro Maju Sejahtera in Bakalan Lor Hamlet, Bligu Village, Ngluwar District, Magelang Regency, Central Java. The method used in this study was a Completely Randomized Block Design (RAKL) consisting of 4 variety treatments including PA-A = Yunan, PA-B = Sultan, PA-C = PA 001, and PA-D = Trinity. Data were analyzed using analysis of variance and continued with the BNJ Test with a level of 5%. The results showed a significant effect on all quantitative parameters such as harvest age, fruit length, fruit diameter, productivity, and storage life. From the study, it can be concluded that the PA 001 variety of bitter melon has qualitative character advantages in the form of leaf shape, leaf blade, leaf apex shape, nodule shape, fruit base shape, and fruit tip shape. The Yunan variety has qualitative advantages in the form of leaf base shape. The Sultan variety has qualitative advantages in the parameters of fruit shape and fruit serration. The Trinity variety tends to excel in qualitative characters such as flower shape. In addition, the PA 001 variety has quantitative advantages in the form of fruit diameter and storage capacity which are significantly different compared to the Yunan, Sultan and Trinity varieties. The PA 001 variety and the Yunan variety obtained significantly different results in the parameters of age from harvest, fruit length, and productivity compared to the Sultan and Trinity varieties